Phenotype of Arabidopsis thaliana semi-dwarfs with deep roots and high growth rates under water-limiting conditions is independent of the GA5 loss-of-function alleles - Barboza Barquero, Luis Orlando (2015)
BACKGROUND AND AIMS: The occurrence of Arabidopsis thaliana semi-dwarf accessions carrying inactive alleles at the gibberellin (GA) biosynthesis GA5 locus has raised the question whether there are pleiotropic effects on other traits at the root level, such as rooting depth. In addition, it is unknown whether semi-dwarfism in arabidopsis confers a growth advantage under water-limiting conditions compared with wild-type plants. The aim of this research was therefore to investigate whether semi-dwarfism has a pleiotropic effect in the root system and also whether semi-dwarfs might be more tolerant of water-limiting conditions. METHODS: The root systems of different arabidopsis semi-dwarfs and GA biosynthesis mutants were phenotyped in vitro using the GROWSCREEN-ROOT image-based software. Semi-dwarfs were phenotyped together with tall, near-related accessions. In addition, root phenotypes were investigated in soil-filled rhizotrons. Rosette growth trajectories were analysed with the GROWSCREEN-FLUORO setup based on non-invasive imaging. KEY RESULTS: Mutations in the early steps of the GA biosynthesis pathway led to a reduction in shoot as well as root size. Depending on the genetic background, mutations at the GA5 locus yielded phenotypes characterized by decreased root length in comparison with related wild-type ones. The semi-dwarf accession Pak-3 showed the deepest root system both in vitro and in soil cultivation experiments; this comparatively deep root system, however, was independent of the ga5 loss-of-function allele, as shown by co-segregation analysis. When the accessions were grown under water-limiting conditions, semi-dwarf accessions with high growth rates were identified. CONCLUSIONS: The observed diversity in root system growth and architecture occurs independently of semi-dwarf phenotypes, and is probably linked to a genetic background effect. The results show that there are no clear advantages of semi-dwarfism at low water availability in arabidopsis.